A flow system for the determination of metal speciation in soil by sequential extraction - J. Shiowatana (2018)
A flow extraction system with on-line and off-line flame atomic absorption spectrometric (FAAS) detection was developed to speed up, facilitate, and improve the accuracy of sequential extraction for metal speciation in solid materials. A flow extraction system with off-line detection was more advantageous than the on-line detection. In the proposed system, extraction was performed in a closed extraction chamber where extractants were flowing through sequentially. The extract from each extraction was collected in 4-10 fractions to obtain a total of approximately 180 ml for subsequent FAAS determination. The system is simple, easy to construct and operate. It has less risk of contamination and human error. A widely used three-step sequential extraction scheme was used to evaluate the novel system by analyzing Ca, Fe, Mn, Cu, and Zn in a certified reference material. The extraction time for three-step sequential extraction of soil sample was 4 h. The analytical results for Ca, Fe, Mn, Cu, and Zn of a soil certified reference material using the proposed system were compared with those of the conventional batch extraction. © 2001 Elsevier Science Ltd. All rights reserved.